Trinitarian theology: Hegelian Vis-A-Vis Advaitic - Briick, Michael von (Journal of Dharma, 1983)
In order to understand Hegel's contribution to the understanding of the Trinity properly we have to go back to Plato's arguments concerning the absoluteness and inexpressibility of God. For Plato it is impossible to think and express the unity of God, because our thinking is limited and determined by the discrimination of subject and predicate, which means duality in any case. To express God as subject can be done only in a predicative determination. Since the realm of the predicate is always wider than the realm of the subject. it is impossible to go beyond this contradiction. God is one (hén estin). But in this sentence the "is" is only copulative and not an expression of existence since otherwise the One would participate in Being, which presupposes dualism. l This One (hén) does not have any name nor can it be known, because it is the subject of any knowledge.